Remembering the Stars of the NFL Glory Years: An Inside Look at the Golden Age of Football - Stewart, Wayne (Rowman & Littlefield Publishers, 2017)
The 1950s and 60s was a golden age for professional football. It was perhaps the toughest and roughest era for the sport, before rules were created to better protect the players, but it was also a time when legends were born. To many football fans this era remains the Glory Years of the NFL, when the stars that roamed the gridiron included the likes of Johnny Unitas, Bart Starr, Jim Brown, and Raymond Berry. In Remembering the Stars of the NFL Glory Years: An Inside Look at the Golden Age of Football, Wayne Stewart tells the story of professional football in the ‘50s and ‘60s through the words of the players themselves. Chapters cover Hall of Famers on both sides of the ball, players who made a lasting impression on the game, and the toughest players on the gridiron. Stewart intertwines profiles of these iconic players with the athletes’ own memories, observations, and anecdotes, including their impressions of teammates and opponents. Two additional chapters consist of humorous quotes and the players’ thoughts on how the game has changed since their heyday. Featuring exclusive interviews with players from the 1950s and ‘60s, Remembering the Stars of the NFL Glory Years provides an inside look at this distinct time in professional football. With a wide range of topics and insights included throughout, this book will both entertain and inform football fans and historians alike.